Implementasi Nilai-Nilai Pendidikan Islam Dalam Pembentukan Karakter Religius Di Sekolah - Meilinda Putri (Mapendis: Jurnal Manajemen Pendidikan Islam, 2023)
Character is a human trait that reflects one’s identity. Character education certainly needs to be given to someone from an early age. Bacause with character education, a balance between society and religion will be created. Islamic education means education that studies knowledge about the Islamic religion which is mandatory for all Muslims. In it there are various Islamic values including moral values, creed, and shari’a. These values need to be given to students at all levels so that in life they do not get lost and do not deviate from their religious teachings. The form of implementing these educational values can be applied by example, habituation, advice, and punishment where these four things will lead students to a better life.